Contemporary world architecture - Pearman, Hugh (London : Phaidon, 1998)
Contemporary World Architecture examines the architectural styles and trends and the social, political and cultural issues that have affected the development of the discipline worldwide since the Modern Movement disintegrated during the 1960s
-- Introduction -- Visual arts : museums and galleries -- Performance : opera houses, theatres and concert halls -- Learning : schools, universities and libraries -- Religion : places of worship -- Consumerism : malls, shops and bars -- Living : houses and apartments -- Workplace : offices and business parks -- Industry : factories and research centres -- Leisure : theme parks, hotels and visitor centres -- Transport : airports, stations and shipping terminals -- Sport : stadia, gymnasia and pools -- The civic realm : public space and structures -- Towers : vertical cities
Includes bibliographical references (pages 488-495) and index
Keywords: Architecture, Modern -- 20th century